Mesoscale controls on particulate matter pollution for a mega city in a semi-arid mountainous environment: Tehran, Iran. (19th March 2010) - Zawar-Reza, Peyman; Appelhans, Tim; Gharaylou, Maryam; Shamsipour, AliAkbar
Tehran, the mega-city capital of Iran, suffers from high concentrations of PM10 throughout the year. Emissions from transport combined with mesoscale atmospheric features related to the mountainous terrain lead to a distinctive diurnal pattern in concentrations. Air quality data from monitoring stations show that the highest concentrations of PM10 are in the morning and evening periods, associated with peak traffic volumes and transition in local meteorology from a stable nocturnal down-slope flow to a daytime upslope regime. There is a clear north-south gradient in PM10 associated with the transport by down-slope winds. A year-long simulation with The Air Pollution Model (TAPM) confirms the mesoscale meteorological regime over Tehran. Simulation results indicate that the peaks in traffic flow and the transition between meteorological regimes contribute to daily PM10 peaks, with the transition playing a relatively minor role.